Sex and Gender Education for Autistic Children to Live Their Daily Lives - Auliyah, Nur Sa'adatul (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Teachers play an important role in the success of the learning process. The role of the teacher is not only as a facilitator but also plays a role in the success of inclusiveness in learning. This study aims to examine the role of teachers in learning toilet training for children with autistic disabilities. Toilet training learning contributes to children's cognitive, emotional and social development. Children with autistic disabilities in the case of this study have more complex difficulties processing learning as well as in understanding the concept of human body and anatomy, which ultimately affects self-perception. But often the difficulty in delivering the teaching of abstract concepts is a major challenge for teachers. This research uses a qualitative method with interviews as its approach. In addition, this study also used a three-stage coding analysis, starting from the open coding, axial coding, and selective coding stages to help interpret the data obtained. The results also show that teachers play a role in building a communicative and safe learning environment for children with autism. In addition, teachers also take a role in collaboration with therapists, and parents in ensuring the success of the learning process.